Biosynthesis of silver nanoparticles from plant extracts: a comprehensive review focused on anticancer therapy - Pandey, Pratibha; Lakhanpal, Sorabh; Bishoyi, Ashok Kumar; Jyothi, S. Renuka; Mishra, Swati; Verma, Meenakshi; Singh, Ajay; Alam, Mir Waqas; Rab, Safia Obaidur; Saeed, Mohd; Khan, Fahad (Frontiers in Pharmacology, 2025)
Cancer is a deadly disease and is one of the primary causes of mortality worldwide. Cancer therapy presents significant challenges, such as chemotherapy resistance, high toxicity, recurrence, and metastasis. As a result, the development of novel therapeutic agents for cancer continues to be a top goal to expand the number of efficient treatments available. The advent of nanotechnology is an important turning point in several scientific disciplines. Owing to the increasing difficulty of this problem, researchers have begun to focus their attention on the possibility of employing plants or extracts from plants as a potential tumor treatment. More than 3,000 medicinal plant species have been documented worldwide for their utilization in cancer treatment. Nevertheless, crude plant extracts lack specificity, and their dosages are not clearly specified. To enhance the therapeutic efficacy of these natural substances, researchers have used them in conjunction with silver nanoparticles (AgNPs). Plants possess intricate phytochemical components including sugars, polyphenols, amino acids, flavonoids, terpenoids, alkaloids, and proteins, which can function as reducing and stabilizing agents. In recent years, the application of plant-derived AgNPs has increased significantly, particularly in cancer treatment. These green-synthesized AgNPs are regarded as outstanding tools for the detection of cancer and targeted drug delivery at the tumor site. By leveraging the distinctive characteristics of nanoparticles and the antioxidant and anticancer qualities of plants, these green-synthesized AgNPs selectively eradicate tumor cells while sparing normal healthy cells. This comprehensive review aimed to summarize the key aspects of plant extracts as anticancer agents, biosynthesis of AgNPs, and recent advancements in the antitumor efficacy of green-synthesized AgNPs.